MULTIPILICATION OPERATION ON VECTOR AND SOME OF THEIR APPLICATION - Singh, V.P. (SCHOOL SCIENCE, 2011)
Multiplication operations in the forms of scalar and vector products have been dealt with in NCERT textbook for Class XII. In this article, we describe further extension of products and discuss some examples related to some physical situations and some specific problems based on these concepts. We close this article by giving some remarks on crucial concepts of projection and distance between skew lines in vector forms.